Development of Potato Nano Carbon as Electrode for Supercapacitors Achieves Green-Sustainable Development Goals - Indri Dayana; Dadan Ramdan; Moranain Mungkin; Habib Satria; Muhammad Fadlan Siregar; Martha Rianna; Juliaster Marbun; Siti Utari Rahayu (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
The development of potato nanocarbon as an electrode from potatoes for supercapacitors will answer the energy needs that are needed and are continuously researched. This research was conducted in the laboratory by giving marinade treatment to potatoes and measured repeatedly and testing was carried out to determine the extent of the carbon content so that potatoes are very good to be used as electrodes with electroplating method. The results obtained were 0.8 grams of potatoes with a very high conductivity increase to 0.97 m S. The result TEM 160 nm after treatment an average size of 100 nm successfully coated on the surface of the particles. FTIR shows a wavelength of 3282.48 cm due to the width of potato absorption and overlapping with the C-H-O group. AAS shows the adsorption capacity of modified potato on metals occurs in the pH range 4.5-5.5. Analysis of potatoes to be made as electrodes with two positive and negative pieces showed better dispersion stability. The electrodes are made and have been tested using a smartphone. The acid in the potato forms a chemical reaction with zinc and copper and when electrons flow from one material to another energy is released.